Comparison of self-reported pain intensity, sleeping difficulty, and treatment outcomes of patients with myofascial temporomandibular disorders by age group: a prospective outcome study - Karibe, Hiroyuki (BMC Musculoskelet Disord, 2014)
BACKGROUND: Subjective symptoms of temporomandibular disorders (TMDs) have rarely been studied by age group. We aimed to compare self-reported pain intensity, sleeping difficulty, and treatment outcomes of patients with myofascial TMDs among three age groups. METHODS: The study population included 179 consecutive patients (151 women and 28 men) who underwent comprehensive clinical examinations at a university-based orofacial pain center. They were classified into myofascial pain subgroups based on the Research Diagnostic Criteria for Temporomandibular Disorders. They were stratified by age group: M1, under 20 years; M2, 20–39 years; and M3, 40 years and older. The patients scored their pretreatment symptoms (first visit) and post-treatment symptoms (last visit) on a form composed of three items that assessed pain intensity and one item that assessed sleeping difficulty. Their treatment options (i.e., pharmacotherapy, physical therapy, and orthopedic appliances) and duration were recorded. All variables were compared between sexes in each group and between the age groups by using the Kruskal–Wallis test, the Mann–Whitney U test, the chi-square test, and analysis of variance (p < 0.05). RESULTS: No significant sex differences were found in any age group. Only sleeping difficulty was significantly different before treatment (p = 0.009). No significant differences were observed in the treatment options or treatment duration. After treatment, the intensity of jaw/face pain and headache and sleeping difficulty was significantly reduced in groups M2 and M3, but only the intensity of jaw/face pain was significantly decreased in group M1. The changes in the scores of pain intensity and sleeping difficulty were not different between the groups. CONCLUSIONS: Pain intensity does not differ by age group, but older patients with myofascial TMDs had greater sleeping difficulties. However, there were no differences between the age groups in the treatment outcomes. Clinicians should carefully consider the age-related characteristics of patients with myofascial TMDs when developing appropriate management strategies.